Polycyclic Aromatic Hydrocarbons in Electrocautery Smoke during Peritonectomy Procedures. (22nd May 2012) - Näslund Andréasson, Sara; Mahteme, Haile; Sahlberg, Bo; Anundi, Helena
Abstract : Objective . This study identified and quantified polycyclic aromatic hydrocarbons (PAHs) in electrocautery smoke during 40 peritonectomy procedures and investigated any correlations and/or differences between levels of PAHs and perioperative variables. Methods . PAHs were measured in personal and stationary sampling by 40 mm Millipore cassettes, for adsorption of both gaseous and particle-bound PAHs. Results . All 16 USEPA priority pollutant PAHs were detected during peritonectomy procedures, naphthalene being the most abundant. For the only two PAHs with Swedish occupational exposure limits (OELs), benzo[a]pyrene and naphthalene, limits were never exceeded. Amount of bleeding was the only perioperative variable that correlated with levels of PAHs. Conclusions . Low levels of PAHs were detected in electrocautery smoke during peritonectomy procedures, and an increased amount of bleeding correlated with higher levels of PAHs. For evaluation of long-term health effects, more studies are needed.